Impact of Digital Tools and Technologies on The Effectiveness of Financial Control - Bochkareva, Ekaterina; Kurdyuk, Petr; Voronenko, Elena; Farikova, Ekaterina (Nexo Revista Científica, 2023)
The article presents dwells on the legal consolidation of the principles of public financial control in the era of digitalization and used as part of the control of digital tools and technologies in the Russian legal field. The study materials include the Constitution of the Russian Federation, Russian and international legal acts (laws and standards), and the websites of Russian public authorities with powers in the field of financial control. To process such materials, the authors used technical and legal analysis as the main method. They conclude that the legal regulation of the principles of public financial control in the Russian Federation is fragmentary. Based on the study of network information resources of Russian public authorities, there is a set of digital tools and technologies used to organize and conduct financial and control activities in a non-contact form. This system includes three main blocks: information systems, personal accounts, and registers. According to the authors, the legal relations that arise in connection with the use of digital tools in financial control are heterogeneous: some are directly related to particular digital technologies (tools); others do not consider a digital product an object of legal relations and assign it an auxiliary value.